Pengaruh Likuiditas, Leverage, dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Manufaktur Sub Sektor Kimia yang Terdaftar di Bursa Efek Indonesia - Saeful Fachri; Niamor Selma Joel; Urfanul Aulia; Willy Nurhayadi (Pajak dan Manajemen Keuangan, 2024)
This research examines the impact of liquidity, leverage, and company size on the financial performance of chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2022 period. Data were collected from secondary sources, specifically www.idx.co.id, using a saturated sampling technique, resulting in 20 company samples. Quantitative analysis was applied to assess these factors' effects on financial performance. Descriptive analysis results indicate that liquidity, leverage, and company size show a moderate relationship with financial performance, with values on a scale of 0.40–0.599. Partial hypothesis testing reveals that liquidity and leverage have positive and significant effects on financial performance, whereas company size does not significantly influence it. In summary, this study concludes that there is a combined influence of liquidity, leverage, and company size on the financial performance of chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2022 period.